Healthcare Accessibility Barriers Confronting Persons with Disabilities in the Kumasi Metropolis - Badu, Eric (2015)
A Thesis Submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences, Kwame Nkrumah University of Science And Technology, in partial fulfillment of the requirements for the degree of Master of Science (Disability, Rehabilitation and Development),